2010
DOI: 10.3390/ijerph7113954
|View full text |Cite
|
Sign up to set email alerts
|

Municipalities Collaborating in Public Health: The Danish Smoking Prevention and Cessation Partnership

Abstract: This study explored the Smoking Prevention and Cessation Partnership (SPCP) which builds upon a collaboration between two Danish municipalities targeted at the prevention of tobacco smoking. The aim of the study was to describe the processes of SPCP, to examine the difficulties this collaboration faced, and to assess how these experiences could be used to improve future partnership collaboration. We employed qualitative methodology comprising 12 semi-structured one-to-one interviews with SPCP’s stakeholders an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Since the process of intersectoral collaboration often requires a new structure, and accordingly, new resources, therefore adequate financial support for these efforts must be considered ( 38 ). In Sweden, Quebec, and South Australia, financial incentives could act as a facilitator for the implementation of health program in all policies ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the process of intersectoral collaboration often requires a new structure, and accordingly, new resources, therefore adequate financial support for these efforts must be considered ( 38 ). In Sweden, Quebec, and South Australia, financial incentives could act as a facilitator for the implementation of health program in all policies ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, since the process of intersectoral collaboration often requires a new structure, and accordingly, new resources, adequate nancial support for these efforts must be provided (64). In a study by Molnar (2016) in Sweden, Quebec, and South Australia, it was indicated that nancial incentives could act as a facilitator for the implementation of the health program in all policies (31).…”
Section: Macro-levelmentioning
confidence: 99%